2002
DOI: 10.3171/jns.2002.96.4.0697
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiographic evidence of sex-linked variations in the circle of Willis and the occurrence of cerebral aneurysms

Abstract: This sex-linked difference in anatomical variations may be correlated to the well-known sex-linked difference in aneurysm distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 45 publications
4
82
2
1
Order By: Relevance
“…The standardized measurement of the confluence of the PCommA provided the real diameters of the distal part of the PCA, and these values did not vary from the ones reported in literature. It would be also worth mentioning here about the differences of the diameter in regards to gender as also pointed out in previous study (Horikoshi et al 2002). The MCA branch traverses the entire extension of the lateral groove, distributing the collaterals that give supply to a large extension of the lateral face of each hemisphere.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The standardized measurement of the confluence of the PCommA provided the real diameters of the distal part of the PCA, and these values did not vary from the ones reported in literature. It would be also worth mentioning here about the differences of the diameter in regards to gender as also pointed out in previous study (Horikoshi et al 2002). The MCA branch traverses the entire extension of the lateral groove, distributing the collaterals that give supply to a large extension of the lateral face of each hemisphere.…”
Section: Discussionsupporting
confidence: 54%
“…The most common anatomical variations observed were the presence of a fetal posterior communicant artery and hypoplasia of the proximal segment of the ACA. These modifications did not seem to differ in different populations, although they could be more regularly associated with the presence of cerebral aneurysms (Horikoshi et al 2002). Overall, MR angiography performs a reliable reproduction of the cerebral vessel calibers and of the Willis polygon branches.…”
Section: Discussionmentioning
confidence: 78%
“…24,28 Instead, a hemodynamic mechanism might be at play; sex-linked variations in the anatomy of and flow dynamics across the circle of Willis have been demonstrated. Horikoshi et al, 16 who studied 131 patients with cerebral aneurysms using MR angiography, demonstrated that anterior communicating artery aneurysms are significantly related to Type A anatomy (no visualization of a unilateral A 1 segment), which is more common in men, whereas ICA aneurysms are associated with Type P anatomy (presence of a fetal type of posterior cerebral artery that was continuously delineated from the ICA through the posterior communicating artery), which is more common in women. 16 In addition, Lindekleiv et al, 27 in a study using computational fluid dynamics, showed that compared with men, women have disproportionately smaller vessel diameters, greater blood flow velocities, and higher wall shear stress at ICA bifurcations, which increases the risk of aneurysm formation.…”
Section: 3134mentioning
confidence: 99%
“….0) to oblong shape (OR 6.2; 95 % CI 1.9-21), and multilobed shape (OR 4.1; 95 % CI 1. [2][3][4][5][6][7][8][9][10][11][12][13][14] were associated with rupture. These ORs decreased after adjustment for size.…”
Section: Introductionmentioning
confidence: 99%